The evolution of personality and individual differences - Buss, David M.; Hawley, Patricia H. (Oxford : Oxford University Press, 2011)
Capturing a scientific change in thinking about personality and individual differences, this volume provides theories and empirical evidence which suggest that personality and individual differences are central to evolved psychological mechanisms and behavioural functioning.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Personality -- Genetic aspects; Personality -- Social aspects; Individual differences; Evolutionary psychology